Pengaruh Pengurusan Landskap Terhadap Emosi Pelajar di Universiti Tun Hussein Onn Malaysia (UTHM) - Wan Apandi, Wan Nur Amirah; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2024)
A development that ignores aspects of landscape management will create an environment that is less attractive, less conducive and capable of affecting the emotions of the people who use it. The state of the landscape in a higher education institution (IPT) can affect the mood of users who are mostly students. This study was carried out to achieve the following objectives; Studying landscape management at UTHM, examining the effects of landscape management at UTHM on the emotions of UTHM students and suggesting improvements that can be made by relevant parties to landscape management at UTHM. The researchers used mixed methods (qualitative and quantitative methods) for data collection. Semi-structured interviews were conducted with the UTHM landscape management and questionnaires were given to students living on campus at UTHM. The interview data was analysed using the content analysis method, while the data gained from questionnaire was analysed using the Statistical Package for the Social Sciences (SPSS) software. The data analysis found that landscape management at UTHM is under the responsibility of the Landscape Unit, Development and Maintenance Office. The landscape concept in the UTHM is "form follows function" which means there is no specific concept. In addition, landscape design does affect students' emotions. Suggestion to increasing the number of shady trees planted in the UTHM to reduce hot temperatures and provide comfort to UTHM students can improve landscape at UTHM. In conclusion, landscape management in the university supports students' ability to live a quality campus life.